Trypanosoma vivax elicits both Th1 and Th2 immunological responses in experimentally infected cattle - Cristina Cholota-Iza; Marbel Torres-Arias; María Augusta Chávez-Larrea; Fausto Bedoya-Paez; Mishell Cisneros-Ruiz; Georgina Morales-Moreno; Jorge Ron-Román; Claude Saegerman; Armando Reyna-Bello (PLoS ONE, 2025)
Bovine trypanosomosis caused by Trypanosoma vivax is a health problem of economic importance in South America. In Ecuador, the presence of T. vivax was first reported in 2018; however, the isolates found in Ecuador are still being studied, mainly on issues related to virulence, pathogenicity, and immune response. To this end, this study aimed to evaluate the cellular and humoral adaptive immune response in vivo in experimentally infected cattle with T. vivax. The study lasted 42 days (with samples collected twice weekly) and was conducted in two cattle experimentally infected with an isolate of T. vivax circulating in Ecuador (TvET1) and two uninfected cattle as controls. Parasitemia was determined by the Brener method and relative gene expression (RGE) of six cytokines was evaluated by RT-qPCR to determine the Th1 response (IFN-γ, TNF-α, IL-1β, IL-12) and the Th2 response (IL-4 and IL-10). Additionally, the total IgG and the IgG1 (Th2) and IgG2 (Th1) subclasses levels were measured using an in-house iELISA. During the study, the animals exhibited four parasitemia peaks concomitant with the cytokines IFN-γ and IL-10. These cytokines, like TNF-α, showed a significant RGE increase (p < 0.05) in infected animals. The presence of total IgG, IgG1 and IgG2 was significant (p < 0.05) in infected animals, and presented a solid monotonic relationship over time. The predominant immunoglobulin subclass was IgG1, and we found that this response was similar to the total IgG. The present study allowed us to highlight the Th response of cattle to T. vivax infection, which is polarized into both a Th1 and a Th2 response. This information contributes to understanding the host-pathogen interaction with strains circulating in Ecuador. The thoroughness of our study can provide the needed knowledge to develop new diagnostic tests and even possible alternatives for vaccine development.